Factorial-experimental investigation of LPBF regimes for VZh159 nickel superalloy grain structure and structural strength optimization - Kyarimov, Rustam R.; Statnik, Eugene S.; Sadykova, Iuliia A.; Frantsuzov, Alexander A.; Salimon, Alexey I.; Korsunsky, Alexander M. (Frontiers in Materials, 2024)
This study investigates the optimization of Laser Powder Bed Fusion (LPBF) process parameters to enhance the mechanical properties of the Russian Ni superalloy VZh159 (a close analogue of IN718) material that commonly used in critical aerospace applications and the corresponding studies of the grain structure within and near the melt pool formed by a single laser track. Through a factorial experimental approach, the influence of laser power and scanning speed on tensile strength, yield strength, and ductility was determined. Metallurgically sound samples (based on hydrostatic weighing data and microscopy, with practically no pores were detected) were obtained with 9 combinations of power and scanning speed, showing significant variation in the tensile strength (in the 1040 1220 MPa range) and yield strength (in the 560 1100 MPa range), which correlated with the cross-sectional area of the single track (for example, the depth of the melt pool varied in the range 410-530 µm), while the average grain size (deduced from Electron Backscatter Diffraction (EBSD) images) remained statistically unchanged. Key findings indicate that the optimal LPBF parameters are a laser power of 250 W, a scanning speed of 600 mm/s, and a hatch distance of 0.12 mm, which together yield the best combination of high tensile strength and ductility. This study provides new insights into the effects of LPBF parameters on microstructure, particularly the formation of the γ' strengthening phase and its correlation with mechanical performance. The research addresses a critical gap in understanding the relationship between LPBF processing conditions and the resultant microstructural and mechanical properties, offering potential improvements in manufacturing efficiency and material performance.